2003
DOI: 10.1109/tac.2003.809148
|View full text |Cite
|
Sign up to set email alerts
|

Composite nonlinear feedback control for linear systems with input saturation: theory and an application

Abstract: We study in this paper the theory and applications of a nonlinear control technique, i.e., the so-called composite nonlinear feedback control, for a class of linear systems with actuator nonlinearities. It consists of a linear feedback law and a nonlinear feedback law without any switching element. The linear feedback part is designed to yield a closed-loop system with a small damping ratio for a quick response, while at the same time not exceeding the actuator limits for the desired command input levels. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
273
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 404 publications
(275 citation statements)
references
References 20 publications
1
273
0
1
Order By: Relevance
“…Then the nonlinear sliding surface defined by (15) is stable. Proof: Refer to the standard sliding mode control method presented in [18] and note that during the sliding mode, 0 = = σ σ  . From (14), it is easy to see that:…”
Section: A Nonlinear Sliding Surface Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Then the nonlinear sliding surface defined by (15) is stable. Proof: Refer to the standard sliding mode control method presented in [18] and note that during the sliding mode, 0 = = σ σ  . From (14), it is easy to see that:…”
Section: A Nonlinear Sliding Surface Designmentioning
confidence: 99%
“…Proof: According to the standard sliding mode control [18], the sliding surface will approach zero in a finite amount of time if the sliding condition…”
Section: Nonlinear Sliding Mode Speed Controller Designmentioning
confidence: 99%
“…Extensive testing by the authors of [12] has shown the search method is likely to be successful if the number of system states, less the number of minimum phase zeros, is not more than three times the number of control inputs, i.e. the inequality n − z ≤ lp (10) holds true for some l ≤ 3, where z is the number of minimum phase zeros. Interestingly, the presence of nonminimum phase zeros does not negatively impact upon the success of the search.…”
Section: B Nonovershooting and Nonundershooting Tracking Controller mentioning
confidence: 99%
“…[8] employed the composite nonlinear feedback (CNF) technique of [9]- [10] and adapted it to the tracking of a general reference signal generated by Robert Schmid and Suzhan Gao are with the Department of Electrical and Electronic Engineering, University of Melbourne, Australia. Lorenzo Ntogramatzidis is with the Department of Mathematics and Statistics, Curtin University, Perth, Australia.…”
Section: Introductionmentioning
confidence: 99%
“…This technique was introduced in [18] for tracking control of a 2 nd order linear system and has been improved for a higher order MIMO linear system in [19]. It was further explored and extended for use in a general multivariable system with input saturation in [20],a linear system with actuator nonlinearities in [21], as well as a hard disk drive servo system and servo positioning system with disturbance in [22][23][24][25]. Recently, CNF has been applied in vehicle dynamics control, particularly for an active suspension system in order to improve suspension deflection, velocity of the car body, tyre deflection, velocity of the car wheel and body acceleration [26] and especially for improving the transient response of the tracking control that has been examined for vehicle yaw rate tracking control.…”
Section: Introductionmentioning
confidence: 99%